General Insurance Subsector Financial Performance in 2020/2021: Does the Covid-19 Pandemic Matter? - Toto Sugiharto (Ilomata International Journal of Tax and Accounting, 2021)
This paper is aimed at analyzing the impact of the covid-19 pandemic on the performance of general insurance subsector in Indonesia. Secondary data obtained from the Indonesia Financial Service Authority which include annual growth rate (year on year) of total asset, technical reserve, investment, equity, and net premium income for the periods between April 2019, 2020 and 2021 to March 2019, 2020 and 2021 were used in this study. Using the dependent sample t-test, it is revealed that the impacts of the covid-19 pandemic on the performance of general insurance subsector were varied. The growth rates of the total asset, total investment, and net premium income of general insurance subsector significantly decreased during the covid-19 pandemic. The decline of these variables was influenced by the covid-19 pandemic. In the meantime, the growth rate of technical reserve and equity were not significantly influenced by the covid-19 pandemic. The growth rate of these variables decreases; however, the degree of decreases was not statistically significant. Findings of the study indicate that further study is required to examine in more detail the factors that potentially affect the performance of the general insurance subsector in relation to the covid-19 pandemic.